Phylogenetically Diverse Aerobic Anoxygenic Phototrophic Bacteria Isolated from Epilithic Biofilms in Tama River, Japan - Hirose, Setsuko (Microbes Environ, 2016)
The diversity of aerobic anoxygenic phototrophic (AAP) bacteria in freshwater environments, particularly in rivers, has not been examined in as much detail as in ocean environments. In the present study, we investigated the phylogenetic and physiological diversities of AAP bacteria in biofilms that developed on submerged stones in a freshwater river using culture methods. The biofilms collected were homogenized and inoculated on solid media and incubated aerobically in the dark. Sixty-eight red-, pink-, yellow-, orange-, or brown-colored colonies were isolated, and, of these, 28 isolates contained the photosynthetic pigment, bacteriochlorophyll (BChl) a. Phylogenetic analyses based on 16S rRNA gene sequences showed that the isolates were classified into 14 groups in 8 operational taxonomic units (OTUs) and distributed in the orders Rhodospirillales, Rhodobacterales, and Sphingomonadales of Alphaproteobacteria and in Betaproteobacteria. Physiological analyses confirmed that none of the representative isolates from any of the groups grew under anaerobic phototrophic conditions. Seven isolates in 4 OTUs showed a 16S rRNA gene sequence identity of 98.0% or less with any established species, suggesting the presence of previously undescribed species of AAP bacteria. Six isolates in 2 other OTUs had the closest relatives, which have not been reported to be AAP bacteria. Physiological comparisons among the isolates revealed differences in preferences for nutrient concentrations, BChl contents, and light-harvesting proteins. These results suggest that diverse and previously unknown AAP bacteria inhabit river biofilms.